Clinical applications of the Human Birth Theory 23rd World Congress of Psychotherapy, Casablanca, 9-11 February 2023 - Autori vari (Il sogno della farfalla, 2025)
This paper presents the contributions of various authors at the Congress of the International Federation for Psychotherapy (now World Federation for Psychotherapy) held in Casablanca in 2023. These presentations were conceived to describe Massimo Fagioli’s legacy, the Human Birth Theory. Starting from the discovery of the disappearance fantasy, going through the theoretical cornerstones, the methodological consequences of the theory, such as the praxis in psychotherapy, the setting and the interpretation of dreams are then discussed. Authors report how Fagioli’s conceptualizations come from his clinical experience with severe psychotic patients and describe the unavoidable link between psychiatry and psychotherapy. All authors shared their training in the Collective Analysis, whose forty-one years of history is described with regard to its main features: cure, training and research.